2010
DOI: 10.4209/aaqr.2009.06.0039
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of Dust Deposition inside Emperor Qin's Terra-Cotta Warriors and Horses Museum

Abstract: Indoor dust deposition, including long-term (>10 years) deposition, short-term (~0.5 year) deposition, and pigment flake samples from partially restored warriors were collected in Emperor Qin's Terra-cotta Warriors and Horses Museum in Xi'an, Shaanxi Province, China. Morphological and elemental analyses of individual particles were performed with scanning electron microscopy and energy dispersive X-ray spectrometry to investigate their composition and potential to damage the statues. Most of the indoor dust wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The reaction between sulfur dioxide and pigment material or deposited particles was found through the crystals of calcium sulfur which were adjacent to the interconnected pits and cracks on the outer surface of pigment flack (Hu et al, 2006). The influence of visitor numbers on the size distributions and particle types were also found in the Exhibition hall (Hu et al, 2006(Hu et al, , 2009(Hu et al, , 2010.…”
Section: Introductionmentioning
confidence: 83%
“…The reaction between sulfur dioxide and pigment material or deposited particles was found through the crystals of calcium sulfur which were adjacent to the interconnected pits and cracks on the outer surface of pigment flack (Hu et al, 2006). The influence of visitor numbers on the size distributions and particle types were also found in the Exhibition hall (Hu et al, 2006(Hu et al, , 2009(Hu et al, , 2010.…”
Section: Introductionmentioning
confidence: 83%
“…Only ammonium sulfate particle could be presumed according to its morphology and EDX spectrum (Hu et al, 2010). In our study, bulk IC analysis provided the mass concentrations of all 8 ions (shown as ions in lower box of Fig.…”
Section: Geological Materialsmentioning
confidence: 99%
“…However, with adopting the above advanced technology, relics are still under destruction by microbe (White and Gass, 1989;Fischer and Dott, 2003) and the condensation of leaked pollutions (White et al, 1989;Nazaroff, Salmon et al, 1990;Nazaroff and Cass, 1991;Weschler, 2001;Yang et al, 2009;Hu et al, 2010;Cao et al, 2011). Thus the evaluation of environmental parameters in the museum should be conducted (Thomson, 1986;Camuffo, 1998;Nazaroff, Weschler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%